THE EFFECT OF PRODUCT QUALITY AND PRICE ON SMARTPHONE CUSTOMERS’ LOYALTY - Fitriani Nur Utami; Mahir Pradana; Taffy Andira Kaljabar (ANALISIS, 2021)
This research was conducted to determine the price and product quality towards consumer loyalty in the city of Bandung. The purpose of this research is to determine and analyze how the price and quality of products provided by Xiaomi to its consumers, as well as the magnitude of the effect of product quality and price simultaneously and partially on consumer loyalty in Bandung. This research uses quantitative methods with descriptive and causal research types. Sampling was done by using non-probability sampling method, purposive sampling type, with the number of respondents as many as 100 people. The data analysis technique used descriptive analysis and multiple linear regression analysis. Based on the results of data analysis with SmartPLS software, it was found that the price and product quality factors together had a positive and significant effect on consumer loyalty in Bandung..